2018
DOI: 10.3390/molecules23040812
|View full text |Cite
|
Sign up to set email alerts
|

Oligo-Alginate with Low Molecular Mass Improves Growth and Physiological Activity of Eucomis autumnalis under Salinity Stress

Abstract: Biopolymers have become increasingly popular as biostimulators of plant growth. One of them, oligo-alginate, is a molecule that regulates plant biological processes and may be used in horticultural practice as a plant growth regulator. Biostimulators are mainly used to improve plant tolerance to abiotic stresses, including salinity. The aim of the study was to assess the effects of salinity and oligo-alginate of various molecular masses on the growth and physiological activity of Eucomis autumnalis. The specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 78 publications
2
23
0
2
Order By: Relevance
“…The most significant differences between PSI-494 and C129 were a smaller main carbohydrate peak and the higher relative abundance of secondary peaks. Previous studies have confirmed that low M w polysaccharides and oligosaccharides from seaweeds were able to stimulate efficiently abiotic stress tolerance in several crop species (Liu et al, 2013;Wu et al, 2016;Singh et al, 2017;Li et al, 2018;Salachna et al, 2018). Our results would also suggest that there is a link between the lower molecular size of carbohydrates inside ANEs and enhanced heat stress tolerance in tomato plants at reproductive stage.…”
Section: Processing Parameters Of Ane Biostimulants Influence Thermotsupporting
confidence: 84%
“…The most significant differences between PSI-494 and C129 were a smaller main carbohydrate peak and the higher relative abundance of secondary peaks. Previous studies have confirmed that low M w polysaccharides and oligosaccharides from seaweeds were able to stimulate efficiently abiotic stress tolerance in several crop species (Liu et al, 2013;Wu et al, 2016;Singh et al, 2017;Li et al, 2018;Salachna et al, 2018). Our results would also suggest that there is a link between the lower molecular size of carbohydrates inside ANEs and enhanced heat stress tolerance in tomato plants at reproductive stage.…”
Section: Processing Parameters Of Ane Biostimulants Influence Thermotsupporting
confidence: 84%
“…However, significant differences were found for inflorescence fresh weight in S. atropurpurea and for physiological parameters in R. hirta, indicating a stronger stimulating effect of the depolymerized gellan of lower M W of 56 kDa. Other studies [21,40] also reported intensified biomass production and photosynthesis following treatment with low M W polysaccharide derivatives. Stronger biological activity of low M W biopolymers may be due to their faster and easier penetration into plant tissues and cells, where they bind with cell membrane receptors and initiate metabolic changes [16,18,21].…”
Section: Discussionmentioning
confidence: 81%
“…AOS as the degradation product of alginate, especially enzymatic hydrolysis products of alginate, is a potent plant elicitor [16]. Previous studies have reported that alginate oligosaccharides are effective in stimulating seed germination [48], promoting root growth [16], enhancing plant tolerance to drought and salt stress [18,49], and alleviating toxic effects of Cd [50]. However, the elicitor-active effect of degradation products against chilling has not been thoroughly elucidated.…”
Section: Discussionmentioning
confidence: 99%